Little Rabbit goes to school - Horse, Harry (Atlanta, Ga. : Peachtree, 2011)
Little Rabbit takes his favorite toy, Charlie Horse, along for his first day of school and when there is trouble, he blames it all on Charlie.
Keywords: First day of school; Schools; Behavior; Rabbits; Toys